Poverty and the Social Sectors: The World Bank in Pakistan 1990-2003. - Birdsall, N; Malik, A; Vaishnav, M (Center for Global Development, 2005)
Over the past decade, the World Bank has consistently emphasized the importance of reducing poverty and improving the delivery of basic social services in Pakistan. Indeed, its resolve to do just that is evident in dozens of official and unofficial studies and assessments, in the Bank’s country assistance strategies, and in the content of its loans. However, a simple fact remains: since the early 1990s, no measurable progress has been made in reducing poverty in Pakistan. In fact, Pakistan remains among the worst countries in the world for a child (and particularly a girl) to be born into. That is so despite its relatively auspicious geographic position, its reasonably good colonial legacy in terms of a professional civil service and the existence of core infrastructure, and the world-class accomplishments of its educated citizens in politics, the arts, and academia.